CORRELATION OF PROPERTIES OF VITA-MEDIUM AND THEIR INTERPRETATIONS IN INTELLIGENT MODEL - A. V. Gulay; V. M. Zaitsev; V. A. Gulay (Системный анализ и прикладная информатика, 2017)
It is shown that the maximally full description of vita-medium with “the substantially sensor system” on the basis of expressed syntax properties implies introduction of complex assertions of experts built on elementary estimates. Natural conditions of determinacy and completeness are put on multiple models by corresponding to all sensor components which control vita-medium properties. The trueness of assertions by experts and inadequacy measure of vita-medium properties provision have been considered in the process of sensor control.It is shown that thermodynamics ideas of informational processes can be used for the generalized description of vita-medium during sensor control of its properties. In order to find out thermodynamic regularities of the censor control procedure the series circuit of conversions is considered: object property – controlled parameter – feature distortion – generalized coordinate – information model. During the high precision control the information quantity is determined with the aid of relative precision logarithm, and in case of comparatively rough determination of vita-medium parameters it depends on the square of sensor control relative precision.Reasons and consequences of distorted sensor images have been considered with the use of technical means of outlines of events and vita-medium properties provision. A contradictory, two-value character of impact on the process of control of extra technical means is shown, which are included between the controlled object and “the subjective sensor system”. Probability of provision of successful collection, procession, accumulation and renewal of information on vita-medium parameters with intelligent system means has been analyzed.